HISTOMORPHOLOGICAL STUDY OF MESONEPHRIC KIDNEY DEVELOPMENT IN PRENATAL STAGES OF RATS (Rattus norvegicus Albinus). - Mirhish, Shakir Mahmood; khalaf, Nidaa hamdi (Diyala Agricultural Sciences Journal, 2016)
The development of mesonephros kidney study wasdone on the rats (Rattus norvegicus Albinus), the study included detection of the timing of appearance of mesonephros kidney. The study revealed that the differentiation and development of the mesonephros kidney began in the rat at 13th day from pregnancy. The study showed that the mesonephros was poorly developed in rat,and the degeneration was began in 15th day of gestation period and end in 17 days gestation period to replace by metanephros (permanent kidney).